2005
DOI: 10.1021/ol051768x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Small-Molecule Assembly through Directional Intramolecular Forces

Abstract: [reaction: see text] Directional intramolecular interactions play a critical role in the self-assembly of donor-sigma-acceptor molecules in solution. Amide functions on the periphery of the tricyclic core stabilize a C3-symmetric monomer conformation by intramolecular hydrogen bonding and dipole-dipole interactions. The molecules are effective organogelators and show long-range ordering in the bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
5
26
1
Order By: Relevance
“…SEM analysis, for example, reveals that fibrous morphologies emerge upon drop-casting a solution of 2 on a glass slide [37]. Moreover, the experimental XRD data reveals an intracolumnar core-to-core distance of 5.2 Å, consistent with the spacings predicted here [10]. Less conclusive is whether intermolecular hydrogen bonding plays a role in the experimentally observed assembly of 2.…”
Section: Assembly Ofsupporting
confidence: 71%
See 4 more Smart Citations
“…SEM analysis, for example, reveals that fibrous morphologies emerge upon drop-casting a solution of 2 on a glass slide [37]. Moreover, the experimental XRD data reveals an intracolumnar core-to-core distance of 5.2 Å, consistent with the spacings predicted here [10]. Less conclusive is whether intermolecular hydrogen bonding plays a role in the experimentally observed assembly of 2.…”
Section: Assembly Ofsupporting
confidence: 71%
“…For 1, NOESY (NMR) experiments in solution have verified the close spatial relationship of the peripheral phenyl groups to the core (NOEs are observed between the aromatic protons and N-␣-CH 2 protons) [9]. For 2, both solution-phase and solid-state NMR studies have revealed the intramolecular hydrogen bonding shown (vide infra) and demonstrated the predicted C 3 -symmetry of the molecule [10].…”
Section: Monomer Structuresmentioning
confidence: 81%
See 3 more Smart Citations